The Influence of Work Environment and Organizational Culture on Organizational Performance Mediated by Learning Agility in Junior High Schools - Muhamad Jibran Fikri (Universitas Negeri Malang, 2023)
Abstract: This study aims to investigate the effect of work environment and organizational learning culture on organizational performance mediated by learning agility in junior high schools. A quantitative approach was used involving 155 teaching staff and administrators as respondents, using questionnaires as the main instrument. Data were analyzed through Macro Process Model 4 to measure direct, indirect, and total effects. The results showed that work environment and organizational learning culture had a significant effect on learning agility, which then mediated the relationship with organizational performance. Learning agility has a central role as a key mediator in this model, enabling organizations to better adapt to change and improve their performance. This research makes a theoretical contribution by enriching the literature related to learning agility and providing empirical evidence in the context of secondary education. In terms of practical implications, this study suggests the importance of creating a supportive work environment and a strong learning culture to improve organizational performance. The limitations of the study lie in the limited coverage of locations as well as the quantitative approach that has not fully explored the qualitative aspects. Further studies are proposed to involve a wider context and additional variables such as leadership style and technology. Keywords: Work environment, organizational learning culture, learning agility, organizational performance.